RESISTANCE EXERCISE TO IMPROVE IMMUNE OF ELDERLY IN NEWNORMAL ERA: REVIEW LITERATURE - Cahyaningsih, Andika Nur; Widyastuti, Zulanda Indah; Febrianti, Lusi; Ramadhani, Alinda Nur (Universitas Muhammadiyah Yogyakarta, 2022)
Introduction – The high rate of transmission of Covid-19 in Indonesia has brought enormous changes to society, especially with the applied of new normal regulation. New normal regulation requires the public to continue carrying out their usual activities by implementing health protocols. The elderly are a population with high risk of covid-19 transmission. Various efforts can be made to maintain the immune system in the new normal era, one of them is by doing exercise. One of the exercises that can be done by the elderly is resistance exercise. Purpose – The purpose of this study was to identify the effect of resistance exercise to increase immunity in the elderly based on evidence based. Methodology/Approach – This study is a literature study that summarizes some relevant literature on the same theme. Literature search using 3 databases: Pubmed, Pedro and BMC Central. Key words used in the literature search included: